FRI0337 Factors associated with poor therapeutic adherence to hydroxychloroquine during systemic lupus. (12th June 2018) - Rozban, Y.; Devilliers, H.; Hié, M.; Pha, M.; Mathian, A.; Cohen-Aubart, F.; Haroche, J.; Hulot, J.-S.; Zahr, N.; Amoura, Z.
Abstract : Background: Poor adherence to medication regimens is a major cause of relapse during systemic lupus erythematosus (SLE). Hydroxychloroquine (HCQ), the main therapy of SLE, has a long half-life. Thus, undetectable blood HCQ concentrations can be used to identify patients who do not take their treatment Objectives: To identify the determinants of poor therapeutic adhesion in patients with SLE. Methods: Case-control, retrospective, monocentric study. The cases were enrolled in our centre from 02/11/2011 to 13/01/2015 according to the following criteria: SLE defined according to ACR classification criteria and blood concentration of HCQ <100 ng/ml after a minimum of 2 months on therapy. For each case, the matched control was a lupus patient, enlisted from our centre the same week, with an HCQ dose greater than or equal to 800 ng/ml. Case and control characteristics were compared using standard tests and a uni-multivariate logistic regression. Results: One hundred and fifty patients were included, 75 cases (68 women) and 75 controls (72 women), with an average age of 35.7 years (±11.3 years) vs 35.6 years (±10.6 years). Most patients had inactive lupus (3 patients had SLEDAI ≥4), 27% of them had benefited from therapeutic education sessions. The average dosage of HCQ was 1110 ng/ml within the control group. In our univariate analysis, nonadherent patients lived significantly further away from the centre than adherent patients (median distance [interquartile range]: 22 11–52 vs 14 km [5.9–35], respectively, p=0.03) and were more likely to be unemployed, (23 vs 8%, respectively, p=0.006). Nonadherent patients had less often benefited from the patient's therapeutic education program (18 vs 35%, respectively, p=0.018), were taking less treatment (3 vs 4, respectively, p=0.008), had a significantly lower level of education (61% compared to 89% of patients with at least a bachelor's degree, p<0.001). In our multivariate analysis, a level of education below the A levels was the strongest factor explaining poor therapeutic adherence, OR (IC 95): 4.09 (1.5–10.8). Conclusions: The main drivers of therapeutic adherence during SLE are socio-economic factors. The least educated and most disadvantaged patients are most likely to display poor therapeutic adherence. Targeted preventive actions and enhanced therapeutic education should be provided to them. Disclosure of Interest: None declared